Prevalence of illicit alcohol consumption and associated factors among adolescents in selected communities of Lusaka, Zambia - Dhally M. Menda; Tom Achoki; Bristol M. Ntebeka; Rosemary K. Zimba; Catherine M. Mulikita; Angela Rizzo; Maynards C. Tembe; Sharon Nkwemu; Rodgers Chilyabanyama; Karen Sichinga; Michael Kachumi; Joel Msafiri Francis; et al. (PLoS ONE, 2026)
Introduction Illicit alcohol (illegally brewed alcohol) consumption among adolescents is an increasing public health problem worldwide, with major impacts on individuals, families, and communities. It’s effects may lead to blindness, poisoning, infection, and other health problems. In Zambia, evidence on the burden of illicit alcohol intake and associated factors is limited, particularly in socioeconomically deprived communities. This study estimated the prevalence and examined the socio- demographic, socio-cultural and socio-economic factors that influence illicit alcohol consumption among adolescents between 10–17 years old in selected unplanned settlements in the city of Lusaka, Zambia. Methods A cross-sectional study was conducted in December 2023, among 331 adolescents who reported alcohol use in 24 selected densely populated peri-urban communities of Lusaka, Zambia. Total enumeration was employed to select participants who met the age criteria and were enrolled in the Screening, Brief Intervention, and Referral to Treatment (SBIRT) program. Face-to-face questionnaire interviews were conducted to collect data on socio-demographic, socio-cultural, socio-economic, and illicit alcohol intake characteristics. Descriptive statistics and graphical presentations were generated, and an investigator-led stepwise multiple logistic regression analysis was performed to identify factors influencing illicit alcohol consumption, with variables with p-values >0.2 removed from the model. Data were analyzed using STATA version 16 MP, and statistical significance was set at p < 0.05. Results The prevalence of illicit alcohol consumption among adolescent alcohol users in the selected Lusaka communities was 42.9% (142/331), with the majority being male (75%). The median age of participants was 16 years (IQR: 15–17). Most adolescents (98.8%, 327/331) had attended school, though only 32% (102/331) had reached secondary level. A large proportion (77.3%, 256/331) lived with their biological parents, while 73.7% (244/331) belonged to large households (more than 10 members). After adjusting for potential confounders, males were more than twice as likely to engage in illicit alcohol intake compared to females (aOR = 2.08, 95% CI: 1.22–3.55, p = 0.005). Conversely, unemployed adolescents were significantly less likely to consume illicit alcohol compared to their employed peers (aOR = 0.52, 95% CI: 0.28–0.90, p = 0.048). Conclusion Illicit alcohol intake among adolescents in peri-urban communities of Lusaka, Zambia, is high and linked to a broad range of risk factors, particularly sex and employment status. Early initiation of comprehensive, multisectoral, community-based strategies with active stakeholder involvement may help mitigate this growing public health problem.